Narrative as Bioethics: The “Fact” of Social Selves and the Function of Consensus - Hester, D. Micah (Cambridge quarterly of healthcare ethics, 2002)
Several months ago, I was walking down the hallway outside our medical school faculty offices and a colleague stopped me to ask a question. He phrased his query in the context of a “hypothetical” case that raised ethical issues for him, and he asked me to respond. I obligingly offered my opinion given the details he presented, ending my comments with the phrase, “at least, that is what I would say.” To this he kindly shot back, “OK, but what is the consensus of medical ethicists?” To be honest, this question caught me off guard. Though his particular dilemma was relatively well-trod territory for many bioethicists, I had done little research on the issue and could not immediately render a response to his latter query.